2022
DOI: 10.1186/s13722-022-00303-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and community changes during COVID-19 and their effects on overdose precursors among rural people who use drugs: a mixed-methods analysis

Abstract: Background Drug overdose rates in the United States have been steadily increasing, particularly in rural areas. The COVID-19 pandemic and associated mitigation strategies may have increased overdose risk for people who use drugs by impacting social, community, and structural factors. Methods The study included a quantitative survey focused on COVID-19 administered to 50 people who use drugs and semi-structured qualitative interviews with 17 people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…Participants indicated that fentanyl was increasingly present in the drug supply during the pandemic. This is consistent with other studies, which have documented shifts in local drug markets during the pandemic including increased fentanyl availability, fentanyl contamination/reduced drug purity, and reduced access to preferred substances among PWUD, both across the USA [ 12 , 13 , 19 , 27 , 36 , 45 ] and internationally [ 11 , 14 , 15 , 38 , 46 ]. The continued proliferation of fentanyl in illicit drug markets underscores the need for states to establish sustainable funding to expand community-based distribution of naloxone [ 47 , 48 ] and fentanyl test strip distribution [ 49 51 ], as well as the need to establish overdose prevention sites [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants indicated that fentanyl was increasingly present in the drug supply during the pandemic. This is consistent with other studies, which have documented shifts in local drug markets during the pandemic including increased fentanyl availability, fentanyl contamination/reduced drug purity, and reduced access to preferred substances among PWUD, both across the USA [ 12 , 13 , 19 , 27 , 36 , 45 ] and internationally [ 11 , 14 , 15 , 38 , 46 ]. The continued proliferation of fentanyl in illicit drug markets underscores the need for states to establish sustainable funding to expand community-based distribution of naloxone [ 47 , 48 ] and fentanyl test strip distribution [ 49 51 ], as well as the need to establish overdose prevention sites [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several investigations in the USA, the UK, and Canada have also documented an increase in behaviors associated with overdose risk among PWUD during the pandemic. Reported overdose risk behaviors included increased drug use amount or frequency, using alone more often, and change in drug type due to pandemic-related supply changes [ 11 19 ]. Further, some studies have documented reduced access to harm reduction and treatment services among PWUD due to pandemic-related closures, further exacerbating overdose risk [ 11 , 13 , 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interviews were conducted before the COVID-19 pandemic and therefore we cannot describe how COVID-19 may have altered the landscape. However, recent studies have shown that the pandemic has exacerbated overdose risk [ 77 , 78 , 79 , 80 ], thus making overdose prevention even more important. Given the semi-structured qualitative nature of the study and the interview guide, we did not systematically collect information about length of drug use, age of first use, criminal legal history, or engagement in drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially noteworthy as structural and drug use pattern changes resulting from the COVID-19 pandemic have led to increased substance use and greater risk for overdose, underscoring the need for additional tools to support recovery during the already high-risk period of community reentry. 23 However, several challenges were described in terms of accessing and maintaining technology following release (see expanded discussion below). We proposed a 2-part intervention that would initially be delivered by a clinician prior to release from jail/prison, followed by 3 months of daily text messages once in the community.…”
Section: Discussionmentioning
confidence: 99%